Silencing of LASS2/TMSG1 enhances invasion and metastasis capacity of prostate cancer cell. Issue 4 (April 2014) - Xu, Xiaoyan; Liu, Beiying; Zou, Pengcheng; Zhang, Yan; You, Jiangfeng; Pei, Fei
ABSTRACT Homo sapiens longevity assurance homolog 2 of yeast LAG1 (LASS2), also known as tumor metastasis suppressor gene 1 (TMSG1), was firstly cloned by our laboratory in 1999. However, its antitumor molecular mechanisms are still unclear. LASS2/TMSG‐1 could directly interact with the C subunit of Vacuolar H+ ATPase (V‐ATPase), which suggested that LASS2/TMSG1 might inhibit the invasion and metastasis through regulating the function of V‐ATPase. In this study, we explored the effect of small hairpin RNA (shRNA) targeting LASS2/TMSG1 on the invasion and metastasis of human prostate carcinoma cell line PC‐3M‐2B4 with low metastatic potential and its functional interaction with V‐ATPase. Silencing of LASS2/TMSG1 gene in PC‐3M‐2B4 cells increased V‐ATPase activity, extracellular hydrogen ion concentration and in turn the activation of secreted MMP‐2 and MMP‐9, which coincided with enhancing cell proliferation, cell survival, and cell invasion in vitro, as well as acceleration of prostate cancer (PCA) growth and lymph node metastases in vivo. Thus we concluded that silencing of LASS2/TMSG1 enhances invasion and metastasis of PCA cell through increase of V‐ATPase activity. These results establish LASS2/TMSG1 as a promising therapeutic target for advanced PCA. J. Cell. Biochem. 115: 731–743, 2014. © 2013 Wiley Periodicals, Inc.